Ulam stability of operators - Brzdek, Janusz; Popa, Dorian; Rasa, Ioan; Xu, Bing (Mathematical analysis and its applications., 2018)
Ulam Stability of Operators presents a modern, unified, and systematic approach to the field. Focusing on the stability of functional equations across single variable, difference equations, differential equations, and integral equations, the book collects, compares, unifies, complements, generalizes, and updates key results. Whenever suitable, open problems are stated in corresponding areas. The book is of interest to researchers in operator theory, difference and functional equations and inequalities, differential and integral equations.